2015
DOI: 10.1016/j.yebeh.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic status epilepticus and neurobehavioral outcomes in critically ill children

Abstract: Purpose Electrographic seizures (ES) and electrographic status epilepticus (ESE) are common in children in the pediatric intensive care unit (PICU) with acute neurologic conditions, and ESE is associated with worse functional and quality of life outcomes. As an exploratory study, we aimed to determine if ESE was associated with worse outcomes using more detailed neurobehavioral measures. Methods Three hundred children with an acute neurologic condition and altered mental status underwent clinically indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
0
44
1
Order By: Relevance
“…Accumulating evidence indicates that high ES exposure is associated with unfavorable short‐ and long‐term neurobehavioral outcomes independent of acute encephalopathy etiology and critical illness severity. Children with acute encephalopathy and ESE (and sometimes also ES) have a higher mortality, worse functional outcome scores on discharge, worse functional outcome at follow‐up, and a higher risk developing subsequent epilepsy . Presumably, more rapid ES identification results in earlier treatment and reduction of seizure burden.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that high ES exposure is associated with unfavorable short‐ and long‐term neurobehavioral outcomes independent of acute encephalopathy etiology and critical illness severity. Children with acute encephalopathy and ESE (and sometimes also ES) have a higher mortality, worse functional outcome scores on discharge, worse functional outcome at follow‐up, and a higher risk developing subsequent epilepsy . Presumably, more rapid ES identification results in earlier treatment and reduction of seizure burden.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of 200 critically ill children managed in our PICU showed that both short-term and long-term outcomes were worse in the presence of electrographic status epilepticus but not electrographic seizures (16, 17, 35). A study by Payne et al indicated that increasing seizure burden was associated with worse short-term neurologic outcomes (19).…”
Section: Discussionmentioning
confidence: 72%
“…1; 9; 10; 12; 1520 Thus, if rapid identification and management of electrographic seizures actually reduced electrographic seizure exposure, this might be a useful neuroprotective strategy. Our initial data suggest that a multi-disciplinary pathway can lead to more rapid management initiation.…”
Section: Discussionmentioning
confidence: 99%